Human poverty – Measuring relative deprivation from basic achievements. A comparative study for 144 world countries in the time span 1990-2010 - Ewa Lechman (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
Poverty – differently defined and measured – still remains one the crucial parts of the world development debate. It`s broadly perceived as multidimensional phenomenon which deprives people from basic capabilities and freedoms, limits their opportunity to educate and fully participate in the labor market contributing to overall country`s socio-economic performance. Referring to seminal works of Sen and many others(see e.g. Morris 1979; Sen 1985, 1992; Desai 1991; Ravallion 1993), we present an specific approach to poverty issues, treating low incomes as consequence – not a cause – of poverty. The main target of the work is twofold. Firstly we aim to develop a new complex measure of relative poverty to set the most recent worldwide poverty estimates. For this purpose we deploy methods based on fuzzy sets (e.g. see works of Zadeh 1965; Dubois&Prade 1980; Bérenger&Verdier-Chouchane 2006), and we apply a wide array of non-income indicators (proxies) explaining level of socio-economic development. Following the logic of fuzzy sets theory, we explain poverty as deprivation from – for example – access to education or improved drinking water. Secondly, we run an analysis on disaggregated data, tracking for factors which contribute mostly to the level of poverty in different countries. Such approach let us to detect most backward areas of human development which shall be in the centre of interest of policy makers. All data applied in the estimates are derived from World Development Indicators Database 2012. The sample covers 144 world economies, and the set time framework is 1990-2010.
Keywords: I32; O15; 330; poverty; fuzzy sets; deprivation; comparative economics